Warehouse Arrangement Improvement Based on 5S Method for CV Javatech Agro Persada - Muhammad Tohari; Manik Mahachandra (Industrial Engineering Online Journal, 2022)
AbstractCV. Javatech Agro Persada is one of the companies engaged in the field of agricultural machine tools, both pre and post-harvest. As it is known that in a company, the storage system has an important role. Therefore, CV Javatech has a warehouse as a place to store supporting equipment for the production process. However, CV Javatech Warehouse experienced overcapacity which forced the company to store 30 of its combine products, namely outside the building. In addition, most of the items in the Javatech warehouse are placed on the floor directly, which makes it difficult for employees to find items. This poor warehouse arrangement system will certainly increase costs for the company. For this reason, this study aims to obtain recommendations for improving warehouse arrangements based on the 5S method. The 5S method is a work attitude application program that emphasizes the management of the physical condition of an organized workplace. Recommendations for improvement are given so that the use of warehouse space is more optimal through the 5S stages, namely at the stages of seiri (sort/concise), seiton (set in order/tidy), seiso (shine/dress), seiketsu (standardize/treat), and shitsuke (sustain/diligent). As much as 23% increase in 5s audit score after repairing the warehouse arrangement.Keywords Improvement, warehouse, 5S, audit and productivity.